On-line capacity recovery method for capacity-fading ferrous sulfide flow battery

By using polysulfides in the electrolyte on the negative electrode side to clean sulfur powder on the positive electrode side in a sulfur-iron flow battery, the problem of battery performance degradation caused by sulfur powder accumulation is solved, and the battery capacity, energy efficiency and lifespan are restored and extended.

CN119297333APending Publication Date: 2025-01-10CHANGSHA HECHU NEW MATERIAL TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411317469.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

During long-cycle operation, sulfur-iron flow batteries experience an increase in ohmic impedance due to the accumulation of sulfur powder on the positive electrode side, which reduces voltage efficiency and coulombic efficiency. Existing technologies cannot effectively address the damage caused by sulfur powder precipitation, thus affecting battery capacity and energy efficiency.

Method used

By using the redox reaction between the polysulfides in the electrolyte on the negative electrode side and the sulfur powder on the positive electrode side without disassembling the battery, the sulfur powder deposited on the separator and carbon felt is cleaned, thereby restoring the battery capacity and energy efficiency.

Benefits of technology

Without disassembling the battery, the discharge capacity and energy efficiency of the sulfur-iron flow battery can be significantly restored to more than 95% of the initial value, extending battery life and reducing restoration costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297333A_ABST
    Figure CN119297333A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of pyrite flow batteries, and provides an online capacity recovery method for a capacity-fading pyrite flow battery, which comprises the following steps: (1) discharging the positive electrode side electrolyte of the capacity-fading pyrite flow battery out of a system for temporary storage, adding a fresh supporting electrolyte solution into a positive electrode liquid storage tank, and circularly cleaning to obtain a positive electrode liquid storage tank; discharging the supporting electrolyte solution; (2) circulating negative electrode side electrolyte to clean sulfur powder and sulfide deposited in a positive electrode cavity, and transferring all negative electrode electrolyte to a negative electrode electrolyte tank after a cleaning target is achieved; (3) adding a fresh supporting electrolyte solution into the positive electrode side liquid storage tank, circularly cleaning, and discharging the supporting electrolyte solution; and (4) adding the temporarily stored positive electrode side electrolyte into the positive electrode side liquid storage tank again to obtain the iron sulfide flow battery with the recovered capacity. The principle that elemental sulfur and polysulfide can be subjected to oxidation-reduction reaction is utilized, the polysulfide contained in the electrolyte on the negative electrode side is used for dissolving sulfur powder separated out from the diaphragm and the carbon felt on the positive electrode side, and the effect of recovering the capacity efficiency of the ferrous sulfide flow battery is achieved through original components in the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sulfide-iron liquid flow batteries, and in particular to an online capacity recovery method for a sulfide-iron liquid flow battery whose capacity decays to less than 95% of an initial value after long-term circulation. Background Art

[0002] Liquid flow battery systems are steadily entering the early stages of commercial development, and various liquid flow battery systems represented by all-vanadium are emerging in an endless stream. However, in the process of expanding commercial production, liquid flow battery systems such as all-vanadium are generally limited by high raw material costs and low resource reserves. The iron-sulfur system is based on earth-abundant elements such as sulfur and iron, and iron has attracted widespread attention due to its low corrosiveness, high chemical and electrochemical stability, and good redox reversibility. The iron-sulfur flow battery uses iron ions and polysulfides to construct a reversible redox reaction to achieve the mutual conversion between chemical energy and electrical energy, and is expected to become the next generation of commercially developed liquid flow battery systems after all-vanadium.

[0003] However, similar ion shuttling as vanadium permeation in all-vanadium flow batteries also inevitably occurs in sulfur-iron flow batteries. When polysulfide ions pass through the separator and reach the positive electrode side, they are transported by Fe 3+ Oxidation generates sulfur powder that adheres to the surface of the diaphragm and carbon felt on the positive electrode side. These precipitated sulfur powders will not be washed away with the circulation of the electrolyte. On the contrary, these sulfur powders will slowly accumulate during the long cycle, resulting in an increase in ohmic impedance, a decrease in voltage efficiency and coulomb efficiency, a significant decrease in energy efficiency and a gradual attenuation of battery capacity. In more serious cases, they may even block the battery flow channel. In order to prevent the shuttling of polysulfides, current research focuses on modifying the diaphragm in a way that ions repel each other, or loading materials that adsorb polysulfides on electrode materials to prevent polysulfides from passing through the diaphragm. However, these methods can only alleviate the precipitation of sulfur powder on the positive electrode side from the source, and cannot solve the damage to battery performance caused by sulfur powder precipitation. In order to restore the capacity and energy efficiency of the sulfur-iron liquid flow battery to at least the initial or near-initial level after the serious attenuation caused by the precipitation of sulfur powder on the positive electrode side, it is necessary to adopt some simple, easy-to-operate means without disassembling the battery to dissolve the sulfur powder precipitated on the diaphragm and carbon felt on the positive electrode side.

[0004] Therefore, there is currently a lack of a regeneration method that can simply and conveniently deal with the problem of sulfur powder precipitation in sulfide-iron flow batteries, so as to extend the service life of sulfide-iron flow batteries. Summary of the invention

[0005] The technical problem to be solved by the present invention is that the accumulation of these sulfur powders during long cycles leads to an increase in ohmic impedance, which reduces voltage efficiency and coulombic efficiency. The shortcomings and defects mentioned in the above background technology are overcome, and an online capacity recovery method for sulfur-iron liquid flow batteries with capacity attenuation is provided.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0007] A method for recovering the online capacity of a capacity-fading iron-sulfur liquid flow battery comprises the following steps:

[0008] (1) temporarily discharging the electrolyte of the positive electrode side of the sulfide-iron flow battery with capacity decay from the system, adding fresh supporting electrolyte solution to the positive electrode storage tank, circulating the supporting electrolyte solution to clean the residual positive electrode electrolyte, and discharging the supporting electrolyte solution after the cleaning target requirement is met;

[0009] (2) The electrolyte on the negative electrode side of the sulfur-iron liquid flow battery with declining capacity is pumped into the positive electrode cavity of the battery through a pipeline, and then discharged from the positive electrode cavity and then led back to the negative electrode electrolyte tank, and the negative electrode electrolyte is circulated to clean the sulfur powder and sulfide deposited in the positive electrode cavity, and all the negative electrode electrolyte is transferred to the negative electrode electrolyte tank after the cleaning target is achieved;

[0010] (3) adding fresh supporting electrolyte solution to the positive electrode storage tank, circulating the supporting electrolyte solution to clean the negative electrode electrolyte remaining in the positive electrode cavity of the battery, and discharging the supporting electrolyte solution after the cleaning target requirement is met;

[0011] (4) Adding the positive electrode electrolyte temporarily stored in step (1) to the positive electrode storage tank again to obtain a sulfide-iron liquid flow battery with restored capacity.

[0012] Preferably, the capacity-faded sulfide-iron liquid flow battery is a sulfide-iron liquid flow battery whose capacity fades to 95% or less of the initial value after a long cycle.

[0013] More preferably, the capacity-faded sulfide-iron flow battery is a sulfide-iron flow battery whose capacity fades to less than 95% of the initial value after long cycles.

[0014] The capacity-fading sulfide iron battery is mainly aimed at the battery whose capacity fades to less than 95% of the initial value after long cycles. After the capacity of the battery is restored by the solution of the present invention, the capacity can be restored to more than 95% of the initial value.

[0015] Preferably, the positive electrode side electrolyte includes a mixture of 0.1-1.6M potassium ferrocyanide and potassium ferrocyanide or sodium ferrocyanide and a supporting electrolyte of 0.1-3M sodium hydroxide or potassium hydroxide, and the negative electrode side electrolyte includes a mixture of 0.1-3.0M disodium disulfide / disodium tetrasulfide and a supporting electrolyte of 0.1-3M sodium hydroxide or potassium hydroxide.

[0016] Preferably, the electrolyte on the negative electrode side of the capacity-faded sulfide iron liquid flow battery contains a supporting electrolyte, and the fresh supporting electrolyte solution added in steps (1) and (3) has the same composition and concentration as the supporting electrolyte solution contained in the electrolyte on the negative electrode side of the capacity-faded sulfide iron liquid flow battery.

[0017] Potassium ferrocyanide / potassium ferrocyanide or sodium ferrocyanide and polysulfide (sodium sulfide / disodium disulfide / disodium tetrasulfide) can arbitrarily form a redox pair, and the redox pair selected for the sulfur iron battery in this patent has a high reaction activity, a high battery energy efficiency, and has the greatest application value in practice.

[0018] Preferably, the electrolyte on the negative electrode side of the capacity-fading sulfide-iron liquid flow battery includes polysulfide or sulfide;

[0019] The electrolyte on the negative electrode side of the capacity-faded sulfide-iron liquid flow battery contains a supporting electrolyte, and the fresh supporting electrolyte solution added in steps (1) and (3) has the same composition and concentration as the supporting electrolyte solution contained in the electrolyte on the negative electrode side of the capacity-faded sulfide-iron liquid flow battery.

[0020] Without disassembling the battery stack, the principle that elemental sulfur and polysulfide can undergo redox reaction is utilized, and with the support of the battery's own circulation system, the sulfur powder precipitated on the diaphragm and carbon felt on the positive electrode side is dissolved to achieve the purpose of cleaning the battery, so that the discharge capacity and energy efficiency of the sulfur-iron liquid flow battery, which have been severely attenuated due to the precipitation of sulfur powder, can be restored to the initial or near-initial level.

[0021] Preferably, whether the cleaning target requirements are met in steps (1), (2) and (3) is determined by the following method:

[0022] The method of sampling and observing the color of the supporting electrolyte solution or performing UV testing on the supporting electrolyte solution is used to determine whether the cleaning target is achieved. If it is clean, stop repeated cleaning; if it is not clean, continue the cyclic cleaning.

[0023] Preferably, in step (2), when the volume of the negative electrode side electrolyte drops to less than 80% of the volume of the positive electrode side electrolyte, the supporting electrolyte solution discharged after the cleaning target requirements are met in step (3) is added to the negative electrode side electrolyte to reduce the volume difference between the negative electrode side electrolyte and the positive electrode side electrolyte.

[0024] Preferably, a mixture of sulfur powder and sodium sulfide is added to the supporting electrolyte solution discharged after the cleaning target requirement is achieved in step (3), and the molar ratio thereof is 1:9 to 3:1, and then added to the negative electrode side electrolyte after being uniformly dissolved. Adding the mixture of sulfur powder and sodium sulfide can further increase the capacity of the negative electrode side electrolyte.

[0025] Preferably, the time for cleaning with the circulating supporting electrolyte solution in steps (1) and (3) is 0.5-2 h, and fresh supporting electrolyte solution is added 1-3 times for each cleaning.

[0026] Preferably, the cleaning time of the circulating negative electrode side electrolyte in step (2) is 0.5-2h.

[0027] Preferably, the electrode of the capacity-fading sulfide-iron liquid flow battery comprises at least one of carbon felt, graphite felt, carbon paper, graphite paper, metal felt or a composite electrode loaded with a catalyst.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The present invention utilizes the principle that sulfur and polysulfide can undergo redox reaction, and uses the polysulfide contained in the electrolyte on the negative electrode side to dissolve the sulfur powder precipitated on the separator and carbon felt on the positive electrode side, thereby achieving the effect of restoring the capacity efficiency of the sulfur-iron liquid flow battery through the original components in the battery;

[0030] (2) The present invention directly solves the existing problem of sulfur powder precipitation on the positive electrode side diaphragm and carbon felt without disassembling the battery stack, thus avoiding damage to them caused by frequent disassembly of the battery; in addition, the present invention does not require replacement of all internal accessories of the battery for capacity recovery, thus saving recovery costs;

[0031] (3) The present invention can effectively restore the discharge capacity and energy efficiency of the sulfide-iron liquid flow battery that have been severely attenuated after long-term cycling by simply cleaning the battery. The degree of recovery is close to 95% or above, which is of great significance for extending the cycle life of the sulfide-iron liquid flow battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 This is a diagram showing the long cycle cleaning effect when the initial charge state is 0% SOC in Example 1;

[0034] Figure 2 This is a diagram showing the effect of long cycle cleaning when the initial SOC state is 100% in Example 2;

[0035] Figure 3 This is a diagram showing the effect of long-cycle cleaning of SOC under the action of a high-performance catalyst in Example 3;

[0036] Figure 4 This is a diagram showing the effect of long cycle with only liquid replacement and no cleaning when the initial SOC state is 100% in Comparative Example 1;

[0037] Figure 5 This is a diagram showing the effect of long-cycle liquid replacement without cleaning under the action of high-performance catalyst in Comparative Example 2;

[0038] Figure 6 This is the effect diagram of the first step of cleaning in Example 1;

[0039] Figure 7 This is a diagram showing the cleaning effect of the third step in Example 1. DETAILED DESCRIPTION

[0040] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0041] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0042] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0043] Example 1

[0044] This embodiment relates to an online capacity recovery method for a capacity-fading sulfide-iron liquid flow battery, comprising the following steps:

[0045] 1. Build a high-performance, low-corrosive, low-cost iron-sulfur flow battery:

[0046] The positive electrode side of the sulfide-iron flow battery is 0.75M potassium ferrocyanide + 1M sodium hydroxide, and the negative electrode side is 0.5M disodium tetrasulfide + 1M sodium hydroxide. The sulfide-iron flow battery is assembled with this formula for long-cycle testing.

[0047] 2. A method for restoring the capacity and energy efficiency of a sulfur-iron flow battery after long cycles:

[0048] When the capacity of the sulfide-iron flow battery decays to less than 95% of the initial value during a long cycle, the battery is cleaned to restore battery performance.

[0049] Step 1: Pour out the electrolyte on the positive electrode side and keep it, add 70ml NaOH solution to the storage tank, start the cycle cleaning for 1h, and notice that the NaOH solution that cleaned the battery for the first time has color. Repeat this operation 3 times, and it can be observed that the NaOH solution that cleaned the battery no longer has color. Take 4ml of the first and third cleaning solutions in a cuvette for UV testing. The UV test shows that the absorption peak of potassium ferrocyanide at 322nm is shown in the first cleaning solution, indicating that potassium ferrocyanide is still contained in the cleaning solution at this time. However, the absorption peak of potassium ferrocyanide is not shown at 322nm in the third cleaning solution, indicating that the residual iron electrolyte in the carbon felt on the positive electrode side, various pipes and pumps has been cleaned.

[0050] Step 2: Pour out the last NaOH cleaning solution of the first step, transfer 70ml Na2S4 solution in the negative electrode storage tank to the positive electrode storage tank, and start the cycle cleaning for 1h to clean the sulfur powder precipitated on the positive electrode diaphragm and carbon felt;

[0051] Step 3: Transfer the Na2S4 electrolyte cleaned in the second step back to the negative electrode, add 70ml NaOH solution to the storage tank, start the cycle cleaning for 1h, and notice that the NaOH solution that cleaned the battery for the first time has color. Repeat this operation 3 times, and it can be observed that the NaOH solution that cleaned the battery no longer has color. Take 4ml of the first and third cleaning solutions in a cuvette for UV testing. The UV test shows that the absorption peaks of disodium tetrasulfide at 300nm and 366nm are shown in the first cleaning solution, indicating that disodium tetrasulfide is still contained in the cleaning solution at this time. However, the absorption peaks of disodium tetrasulfide are not shown at 300nm and 366nm in the third cleaning solution, indicating that the residual sulfur electrolyte in the carbon felt on the negative electrode side, various pipes and pumps have been cleaned at this time.

[0052] Step 4: Pour out the last NaOH cleaning solution in step 3, add the positive electrode electrolyte retained in step 1 to the reservoir, start the cycle and wait for 30 minutes to fully wet the battery, then restart the long cycle test on the battery.

[0053] like Figure 1 As shown in , during the first long cycle of the battery of this embodiment, sulfur powder gradually precipitated on the positive electrode side diaphragm and carbon felt, causing the discharge capacity and energy efficiency of the sulfur-iron battery to slowly decay during the later cycles, especially the discharge capacity severely decayed to nearly 0. After cleaning the battery and starting the second long cycle, the capacity can be restored to about 95% before the first long cycle decay, and the energy efficiency can be restored to about 97% before the first long cycle decay.

[0054] Figure 6 This is the effect diagram of the first step of cleaning in Example 1; Figure 7This is the cleaning effect diagram of the third step in Example 1. Figure 6 , 7 It can be seen that the battery capacity has been significantly improved after cleaning.

[0055] Example 2

[0056] This embodiment relates to an online capacity recovery method for a capacity-fading sulfide-iron liquid flow battery, comprising the following steps:

[0057] 1. Build a high-performance, low-corrosive, low-cost iron-sulfur flow battery:

[0058] The positive electrode side is 0.3M potassium ferrocyanide + 1M sodium hydroxide, and the negative electrode side is 0.5M disodium disulfide + 1M sodium hydroxide. The sulfur-iron liquid flow battery is assembled with this formula for long cycle testing.

[0059] 2. A method for restoring the capacity and energy efficiency of a sulfur-iron flow battery after long cycles:

[0060] When the capacity of the sulfide-iron flow battery decays to less than 95% of the initial value during a long cycle, the battery is cleaned to restore battery performance.

[0061] Step 1: Pour out the electrolyte on the positive electrode side and keep it, add 70ml NaOH solution to the storage tank, start the cycle cleaning for 1h, and notice that the NaOH solution that cleaned the battery for the first time has color. Repeat this operation 3 times, and it can be observed that the NaOH solution that cleaned the battery no longer has color. Take 4ml of the first and third cleaning solutions in the cuvette for UV testing. The UV test shows that the first cleaning solution has absorption peaks of potassium ferrocyanide at 330nm and 420nm, indicating that the cleaning solution still contains potassium ferrocyanide. However, the third cleaning solution does not show absorption peaks of potassium ferrocyanide at 330nm and 420nm, indicating that the residual iron electrolyte in the carbon felt on the positive electrode side, various pipes and pumps has been cleaned.

[0062] Step 2: Pour out the last NaOH cleaning solution of the first step, transfer 70ml Na2S4 solution in the negative electrode storage tank to the positive electrode storage tank, and start the cycle cleaning for 1h to clean the sulfur powder precipitated on the positive electrode diaphragm and carbon felt;

[0063] Step 3: Transfer the Na2S4 electrolyte cleaned in the second step back to the negative electrode, add 70ml NaOH solution to the storage tank, start the cycle cleaning for 1h, and notice that the NaOH solution that cleaned the battery for the first time has color. Repeat this operation 3 times, and it can be observed that the NaOH solution that cleaned the battery no longer has color. Take 4ml of the first and third cleaning solutions in the cuvette for UV testing. The UV test shows that the absorption peaks of disodium disulfide at 300nm and 366nm are shown in the first cleaning solution, indicating that disodium disulfide is still contained in the cleaning solution at this time. However, the absorption peaks of disodium disulfide are not shown at 300nm and 366nm in the third cleaning solution, indicating that the residual sulfur electrolyte in the carbon felt on the negative electrode side, various pipes and pumps have been cleaned at this time.

[0064] Step 4: Pour out the last NaOH cleaning solution in step 3, add the positive electrode electrolyte retained in step 1 to the reservoir, start the cycle and wait for 30 minutes to fully wet the battery, then restart the long cycle test.

[0065] like Figure 2 As shown in , during the first long cycle of the battery of this embodiment, the discharge capacity and energy efficiency both show a tendency to decay in the later stage. After cleaning, the capacity and energy efficiency can be restored to about 97% before the first long cycle decay.

[0066] Example 3

[0067] This embodiment relates to an online capacity recovery method for a capacity-fading sulfide-iron liquid flow battery, comprising the following steps:

[0068] 1. Construct a high-performance, low-corrosive, low-cost iron-sulfur flow battery containing catalysts or additives:

[0069] The positive electrode side is 0.3M potassium ferrocyanide + 1M sodium hydroxide, the negative electrode side is 0.5M disodium disulfide + 1M sodium hydroxide, and catalysts such as titanium cyanine iron are used on the negative electrode side to improve battery performance. This formula is used to assemble the iron-sulfur liquid flow battery for long-cycle testing.

[0070] 2. A method for restoring the capacity and energy efficiency of a sulfur-iron flow battery after long cycles:

[0071] When the capacity of the sulfide-iron flow battery decays to less than 95% of the initial value during a long cycle, the battery is cleaned to restore battery performance.

[0072] Step 1: Pour out the electrolyte on the positive electrode side and keep it, add 70ml NaOH solution to the storage tank, start the cycle cleaning for 1h, and notice that the NaOH solution that cleaned the battery for the first time has color. Repeat this operation 3 times, and it can be observed that the NaOH solution that cleaned the battery no longer has color. Take 4ml of the first and third cleaning solutions in the cuvette for UV testing. The UV test shows that the first cleaning solution has absorption peaks of potassium ferrocyanide at 330nm and 420nm, indicating that the cleaning solution still contains potassium ferrocyanide. However, the third cleaning solution does not show absorption peaks of potassium ferrocyanide at 330nm and 420nm, indicating that the residual iron electrolyte in the carbon felt on the positive electrode side, various pipes and pumps has been cleaned.

[0073] Step 2: Pour out the last NaOH cleaning solution of the first step, add 70ml of 0.1mol / L Na2S4 solution to the storage tank, and start the cycle cleaning for 2h to clean the sulfur powder precipitated on the positive electrode side diaphragm and carbon felt;

[0074] Step 3: Pour out the last Na2S4 cleaning solution of the second step and keep it as the cleaning solution for the future. Add 70ml of NaOH solution to the storage tank, start the cycle cleaning for 1h, and notice that the NaOH solution that cleaned the battery for the first time has color. Repeat this operation 3 times, and it can be observed that the NaOH solution that cleaned the battery no longer has color. Take 4ml of the first and third cleaning solutions in the cuvette for UV testing. The UV test shows that the absorption peaks of disodium disulfide are at 300nm and 366nm in the first cleaning solution, indicating that the cleaning solution still contains disodium disulfide at this time. However, the absorption peaks of disodium disulfide are not shown at 300nm and 366nm in the third cleaning solution, indicating that the residual sulfur electrolyte in the carbon felt on the negative electrode side, various pipes and pumps have been cleaned at this time.

[0075] Step 4: Pour out the last NaOH cleaning solution in step 3, add the positive electrode electrolyte retained in step 1 to the reservoir, start the cycle and wait for 30 minutes to fully wet the battery, then restart the long cycle test.

[0076] like Figure 3As shown in the figure, catalysts such as iron phthalocyanine can promote the electrochemical conversion of polysulfides and improve the comprehensive performance of sulfur-iron flow batteries, while carbon materials such as XC-72 carbon black and activated carbon have an adsorption effect on polysulfides, so they can alleviate the shuttling of polysulfides. Compared with unloaded sulfur-iron flow batteries, the degree of sulfur powder precipitation after the same operation time will be reduced, and the amount of sulfur powder precipitated on the surface of the positive electrode side diaphragm and carbon felt is relatively small. The rate of discharge capacity and energy efficiency decay is slowed down, which is conducive to shortening the cleaning time. However, the sulfur powder precipitated on the surface of the positive electrode side diaphragm and carbon felt will slowly accumulate during the long cycle process, which will inevitably lead to discharge capacity decay. After cleaning the sulfur-iron battery, the capacity can be restored to about 97% before the first long cycle decay, and the energy efficiency can be restored to about 98% before the first long cycle decay.

[0077] Comparative Example 1

[0078] This comparative example relates to an online capacity recovery method for a capacity-fading sulfide-iron liquid flow battery, comprising the following steps:

[0079] 1. Build a high-performance, low-corrosive, low-cost iron-sulfur flow battery:

[0080] Step 1: The positive electrode side is 0.3M potassium ferrocyanide + 1M sodium hydroxide, and the negative electrode side is 0.5M disodium disulfide + 1M sodium hydroxide. Use this formula to assemble the sulfur-iron liquid flow battery for long cycle testing.

[0081] Step 2: When the capacity of the sulfur-iron flow battery decays to less than 95% of the initial value, replace the electrolyte on both sides with fresh 70ml sulfur-iron electrolyte and start the long cycle test again;

[0082] like Figure 4 As shown, after the first long-cycle discharge capacity and energy efficiency decay of the comparative battery, the capacity and energy efficiency were able to recover to about 91% before decay by replacing the electrolytes on both sides, but soon decayed again to almost 0.

[0083] Comparative Example 2

[0084] This comparative example relates to a method for restoring the capacity and energy efficiency of a sulfide-iron liquid flow battery after a long cycle, comprising the following steps:

[0085] 1. Construct a high-performance, low-corrosive, low-cost iron-sulfur flow battery containing catalysts or additives:

[0086] Step 1: The positive electrode side is 0.3M potassium ferrocyanide + 1M sodium hydroxide, the negative electrode side is 0.5M disodium disulfide + 1M sodium hydroxide, and catalysts such as titanium cyanine iron are used on the negative electrode side to improve battery performance. This formula is used to assemble the sulfur-iron liquid flow battery for long-cycle testing.

[0087] Step 2: When the capacity of the sulfur-iron flow battery decays to less than 95% of the initial value, replace the electrolyte on both sides with fresh 70ml sulfur-iron electrolyte and start the long cycle test again;

[0088] like Figure 5 As shown, after the catalyst is loaded on the negative electrode, the battery discharge capacity and energy efficiency decay trend slows down. After replacing the electrolyte on both sides, the discharge capacity and energy efficiency can only be restored to about 93% before decay, but then the decay rate is also very fast, and the performance cannot be effectively restored in the long term.

Claims

1. A method for recovering the capacity of a sulphur-iron liquid flow battery with capacity attenuation, characterized in that: The following steps are involved: (1) temporarily discharging the electrolyte of the positive electrode side of the sulfide-iron flow battery with capacity decay from the system, adding fresh supporting electrolyte solution to the positive electrode storage tank, circulating the supporting electrolyte solution to clean the residual positive electrode electrolyte, and discharging the supporting electrolyte solution after the cleaning target requirement is met; (2) The electrolyte on the negative electrode side of the sulfur-iron liquid flow battery with declining capacity is pumped into the positive electrode cavity of the battery through a pipeline, and then discharged from the positive electrode cavity and then led back to the negative electrode electrolyte tank, and the negative electrode electrolyte is circulated to clean the sulfur powder and sulfide deposited in the positive electrode cavity, and all the negative electrode electrolyte is transferred to the negative electrode electrolyte tank after the cleaning target is achieved; (3) adding fresh supporting electrolyte solution to the positive electrode storage tank, circulating the supporting electrolyte solution to clean the negative electrode electrolyte remaining in the positive electrode cavity of the battery, and discharging the supporting electrolyte solution after the cleaning target requirement is met; (4) Adding the positive electrode electrolyte temporarily stored in step (1) to the positive electrode storage tank again to obtain a sulfide-iron liquid flow battery with restored capacity.

2. The recovery method according to claim 1, characterized in that: The capacity-faded sulfide-iron liquid flow battery is a sulfide-iron liquid flow battery whose capacity fades to 95% or less of the initial value after a long cycle.

3. The recovery method according to any one of claims 1 or 2, characterized in that: The electrolyte on the negative electrode side of the capacity-faded sulfide-iron liquid flow battery includes polysulfide or sulfide; The electrolyte on the negative electrode side of the capacity-faded sulfide-iron liquid flow battery contains a supporting electrolyte, and the fresh supporting electrolyte solution added in steps (1) and (3) has the same composition and concentration as the supporting electrolyte solution contained in the electrolyte on the negative electrode side of the capacity-faded sulfide-iron liquid flow battery.

4. The recovery method according to claim 3, characterized in that: The positive electrode side electrolyte includes a mixture of 0.1-1.6M potassium ferrocyanide and potassium ferrocyanide or sodium ferrocyanide and 0.1-3M sodium hydroxide or potassium hydroxide supporting electrolyte, and the negative electrode side electrolyte includes a mixture of 0.1-3.0M disodium disulfide and disodium tetrasulfide and 0.1-3M sodium hydroxide or potassium hydroxide supporting electrolyte.

5. The recovery method according to any one of claims 1 or 2, characterized in that: Whether the cleaning target requirements described in steps (1), (2) and (3) have been met can be determined by the following method: The method of sampling and observing the color of the supporting electrolyte solution or performing UV testing on the supporting electrolyte solution is used to determine whether the cleaning target is achieved. If it is clean, stop repeated cleaning; if it is not clean, continue the cyclic cleaning.

6. The recovery method according to any one of claims 1 or 2, characterized in that: In step (2), when the volume of the negative electrode side electrolyte drops to less than 80% of the volume of the positive electrode side electrolyte, the supporting electrolyte solution discharged after the cleaning target requirements are met in step (3) is added to the negative electrode side electrolyte to reduce the volume difference between the negative electrode side electrolyte and the positive electrode side electrolyte.

7. The recovery method according to claim 6, characterized in that: A mixture of sulfur powder and sodium sulfide is added to the supporting electrolyte solution discharged after the cleaning target requirement is achieved in step (3), with the molar ratio of sulfur powder and sodium sulfide being 1:9 to 3:1, and then added to the negative electrode electrolyte after being uniformly dissolved.

8. The recovery method according to any one of claims 1 or 2, characterized in that: The time for circulating the supporting electrolyte solution for cleaning in steps (1) and (3) is 0.5-2 hours, and fresh supporting electrolyte solution is repeatedly added 1-3 times for each cleaning.

9. The recovery method according to any one of claims 1 or 2, characterized in that: The cleaning time of the circulating negative electrode side electrolyte in step (2) is 0.5-2h.

10. The recovery method according to any one of claims 1 or 2, characterized in that: The electrode of the capacity-fading sulfide-iron liquid flow battery includes at least one of carbon felt, graphite felt, carbon paper, graphite paper, metal felt or a composite electrode loaded with a catalyst.